Method and system for improving performance of mesophase pitch carbon fiber

By pretreating and post-treating the mesophase asphalt carbon fiber, including melting into spinning, preoxidation, carbonization and activation treatment, the problems of difficult preparation and general performance of mesophase asphalt carbon fiber are solved, and the mechanical properties and conduction properties are improved.

CN119877151APending Publication Date: 2025-04-25CHANGZHOU TEXTILE GARMENT INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510099554.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the mesophase asphalt carbon fiber is difficult to prepare and has a general performance during use.

Method used

Pretreatment of the mesophase bitumen, including heating, filtration and degassing, followed by melting into spinning, preoxidation, carbonization and activation, and finally cleaning, drying and sizing to improve the radial structure and surface energy of the carbon fibers.

Benefits of technology

It significantly improves the mechanical properties and conductivity of mesophase asphalt carbon fiber, improves its adhesion properties to the matrix material, and meets the application needs of high-performance composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877151A_ABST
    Figure CN119877151A_ABST
Patent Text Reader

Abstract

The invention discloses a method and system for improving the performance of mesophase pitch carbon fibers, and the method comprises the following steps: selecting mesophase pitch as a raw material, carrying out pretreatment, melting the pretreated mesophase pitch to form spun yarns, carrying out pre-oxidation treatment on the spun yarns to form pre-oxidized fibers, and drying the pre-oxidized fibers to obtain the mesophase pitch carbon fibers. Feeding the pre-oxidized fiber into a carbonization furnace for carbon treatment and activation treatment after carbonization, and cleaning, drying and sizing the activated carbon fiber. The mesophase pitch-based carbon fiber is prepared by using spinneret plates with different length-diameter ratios and pore diameters and a spinneret plate self-designed according to an outlet swelling effect, the influence of the spinneret plate structure on the radial structure and performance of the pitch-based carbon fiber is researched, and the pitch-based carbon fiber is prepared by controlling and improving the radial structure of the mesophase pitch-based carbon fiber. And through plasma surface treatment, the surface wettability and the interface bonding capacity of the carbon fiber are improved, and the adhesion performance of the carbon fiber and a base material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber, and in particular relates to a method and a system for improving the performance of mesophase asphalt carbon fiber. Background Art

[0002] With the rapid development of science and technology, carbon fiber is not only used as a reinforcement in composite materials, but also widely used in civil electronic equipment, high-rise buildings, integrated circuits, high-speed transportation, information engineering, marine engineering, new energy, life sciences and national defense construction. Carbon fiber also has good biocompatibility. People can also adjust the surface functional groups, chemical properties, mechanical properties and usage forms of carbon fiber according to needs, so that it can be used in chemical industry, food, biopharmaceuticals, wastewater biological treatment and fixed microbial cells. Carbon fiber and its composite materials are one of the main new materials of this century.

[0003] Mesophase pitch-based carbon fiber (MPCF) is widely used in aerospace, automobile, military, electronic devices, biology, energy and other fields due to its excellent properties such as low density, high modulus and high thermal conductivity. However, compared with PAN-based carbon fiber, the tensile and compressive strength of mesophase pitch-based carbon fiber is lower, which not only makes its preparation process difficult, but also seriously affects its wider application. Therefore, it is worth looking forward to a method that can improve the mechanical properties of mesophase pitch-based carbon fiber without affecting its conductivity and modulus.

[0004] The Chinese patent application number 201410468654.7 discloses a method for preparing a novel mesophase asphalt-based composite carbon fiber, the preparation steps of which are: firstly, using graphene as filler, the mesophase asphalt and graphene are fully mixed by crushing and ultrasonic stirring; then, melt spinning is performed and the graphene-doped mesophase asphalt-based composite carbon fiber is obtained by infusibility, carbonization, and graphitization. The present invention makes full use of the special two-dimensional structure and high conductive mechanical properties of graphene, and effectively improves the cross-sectional structure of the mesophase asphalt-based carbon fiber by compounding with the mesophase asphalt. Compared with the mesophase asphalt-based carbon fiber without graphene doping, the mechanical properties and conductive properties of the composite carbon fiber are greatly improved, but the carbon fiber produced by this method has low surface energy and poor activity. Summary of the invention

[0005] The purpose of the present invention is to provide a method and system for improving the performance of mesophase pitch carbon fibers. The technical problem to be solved is that the mesophase pitch carbon fibers in the prior art are difficult to prepare during use and have average performance.

[0006] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for improving the performance of mesophase pitch carbon fibers, comprising: Selecting mesophase asphalt as raw material for pretreatment; Melting the pretreated mesophase pitch into spinning fibers; Performing a pre-oxidation treatment on the spinning to form pre-oxidized fibers; The pre-oxidized fibers are fed into a carbonization furnace for carbonization and activation after carbonization; The activated carbon fibers are cleaned, dried and sized.

[0007] By using spinnerets with different aspect ratios and apertures and spinnerets designed according to the outlet swelling effect to prepare mesophase asphalt-based carbon fibers, the influence of spinneret structure on the radial structure and properties of asphalt-based carbon fibers was studied. The performance of mesophase asphalt carbon fibers was improved by controlling and improving the radial structure of the mesophase asphalt carbon fibers. The surface wettability and interfacial bonding ability of carbon fibers were improved through plasma surface treatment, and their adhesion to the matrix material was significantly improved.

[0008] Optionally, the pretreatment of the raw materials includes: heating the intermediate phase asphalt to a set temperature to make it in a molten state, using a filtering device to remove impurities and insoluble matter in the intermediate phase in the molten state, transferring the filtered intermediate phase asphalt to a vacuum container for degassing, removing impurities through pretreatment, and allowing bubbles and volatile substances in the asphalt to overflow through degassing.

[0009] Optionally, spinnerets with different aspect ratios and apertures are selected, and the spinnerets are designed according to the outlet expansion effect to optimize the radial structure of the fiber. The spinning parameters are adjusted to improve the fiber uniformity, and the pretreated mesophase asphalt is extruded through the spinneret holes to form continuous fibers. The extrusion speed and fineness of the fibers can be controlled by adjusting the pressure. The crystallinity and orientation of the fibers can be adjusted by controlling the spinning speed and cooling conditions to improve the mechanical properties of the fibers.

[0010] Optionally, the pre-oxidation treatment includes: evenly laying the fibers obtained by melt spinning on the conveyor belt of the pre-oxidation furnace, ensuring that there are gaps for air circulation between the fibers so that the air can circulate fully and the fibers are heated evenly, sending the fibers into the pre-oxidation furnace for heating, controlling the heating rate between 1 degree and 2 degrees / min until it rises to 200 degrees to 250 degrees, and maintaining a certain insulation time after reaching the pre-oxidation temperature. The pre-oxidation time is 1-2 hours, so that the intermediate phase asphalt molecules in the fiber can fully undergo oxidation reaction.

[0011] Optionally, the carbon treatment includes: placing the pre-oxidized fibers in a carbonization furnace and heating them, controlling the heating rate to be 2 to 3 degrees per minute, first controlling the temperature to be carbonized at a low temperature of 600 to 700 degrees, and holding the temperature for 1 to 2 hours, and then raising the temperature to 1000 to 1200 degrees, and setting the holding time to 2 to 3 hours. By carbonizing the fibers, non-carbon elements are removed to form a preliminary carbon fiber structure, thereby improving the crystallinity and strength of the carbon fibers, and continuously introducing inert gas during the carbonization process to ensure the stability of the intracranial atmosphere.

[0012] Optionally, the activation treatment includes: placing the carbon treated carbon fiber in a plasma treatment device, turning on the device to bombard the carbon fiber surface with high energy particles to generate polar groups and free radicals on the surface, and the bombardment time is set to 30 to 60 minutes, the power is set to 500 to 1000 watts, and the high energy particles in the plasma are used to bombard the carbon fiber surface to generate polar groups and free radicals on the surface to increase the surface energy. At the same time, plasma treatment can also remove impurities and pollutants on the surface of the carbon fiber, making the surface cleaner.

[0013] Optionally, cleaning, drying and sizing the activated carbon fiber specifically include: Cleaning: Select a suitable cleaning agent and use one or more methods of immersion, spraying or ultrasonic cleaning. The cleaning time is 30 to 60 minutes; Drying: drying the cleaned carbon fiber in one or more ways of a hot air drying oven or a vacuum drying oven, wherein the drying temperature is set at 80 to 120 degrees and the drying time is set at 2 to 4 hours; Sizing: Select a suitable sizing agent and use one or more methods of dipping, spraying or brushing to apply sizing, and after the sizing is completed, dry it until the slurry is completely dry.

[0014] By post-processing the carbon fiber, impurities and moisture are preferably removed, the stability of the drying environment is ensured, the influence of temperature fluctuations or humidity changes on the drying effect of the carbon fiber is avoided, and the bundling is improved. The sizing agent can improve the compatibility of the carbon fiber and the matrix, enhance the bonding strength between the carbon fiber and the matrix, and improve the overall performance of the composite material.

[0015] In a second aspect, the present invention further provides a system for improving the performance of mesophase pitch carbon fiber according to any one of the first aspects, comprising: a) a gas pressure single hole spinning machine for preparing mesophase pitch carbon fiber by spinning process; b) manufacturing spinnerets with different aspect ratios and apertures to optimize the radial structure of the fiber; c) a plasma surface treatment device including a high energy plasma source for modifying the surface of carbon fibers to increase their surface energy and activity; d) Control module, used to adjust spinning parameters and surface treatment parameters, including temperature, pressure, air pressure, power and treatment time, to achieve process optimization.

[0016] By improving the radial structure of the mesophase pitch carbon fiber, it has higher uniformity and mechanical properties. By optimizing the spinning process and surface treatment technology, the overall performance of the carbon fiber is improved to meet the application requirements of high-performance composite materials.

[0017] Optionally, the preparation of spinnerets with different aspect ratios and apertures specifically includes: The shape and size of the spinneret holes of the spinneret are determined according to the mathematical model. Through numerical simulation and experimental verification, the control effects of spinnerets with different shapes and sizes on the outlet swell effect are compared. According to the experimental results, the spinneret design is adjusted until the expected outlet swell control effect is achieved.

[0018] Optionally, the plasma surface treatment method specifically includes: a) Adjust the plasma power to 10 to 200 W; b) Processing in a vacuum environment with a pressure range of 0.01 to 1 Torr; c) The processing time is between 10 and 300 seconds.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The method for improving the performance of mesophase asphalt carbon fiber of the present invention removes impurities therein through pretreatment, and allows bubbles and volatile substances in the asphalt to overflow through degassing treatment. By controlling the spinning speed and cooling conditions, the crystallinity and orientation of the fiber can be adjusted to improve the mechanical properties of the fiber. By carbonizing the fiber, non-carbon elements are removed to form a preliminary carbon fiber structure, thereby improving the crystallinity and strength of the carbon fiber. By continuously introducing inert gas during the carbonization process, the stability of the intracranial atmosphere is ensured. The high-energy particles in the plasma are used to bombard the surface of the carbon fiber to generate polar groups and free radicals on the surface, thereby improving the surface energy.

[0020] 2. The method of improving the performance of mesophase asphalt carbon fiber of the present invention preferentially removes impurities and moisture through post-processing of carbon fiber, ensures the stability of the drying environment, avoids the influence of temperature fluctuations or humidity changes on the drying effect of carbon fiber, improves the bundling, and the sizing agent can improve the compatibility of carbon fiber and matrix, enhance the bonding strength between carbon fiber and matrix, and improve the overall performance of composite material.

[0021] 3. The system for improving the performance of mesophase asphalt carbon fibers of the present invention improves the radial structure of the mesophase asphalt carbon fibers to make them have higher uniformity and mechanical properties, and improves the overall performance of the carbon fibers by optimizing the spinning process and surface treatment technology to meet the application requirements of high-performance composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention. Embodiment 1

[0024] like Figure 1 As shown, a method for improving the performance of mesophase asphalt carbon fiber is provided, which is characterized by: comprising selecting mesophase asphalt as raw material for pretreatment, melting the pretreated mesophase asphalt into spinning, pre-oxidizing the spinning to form pre-oxidized fibers, sending the pre-oxidized fibers into a carbonization furnace for carbon treatment and activation treatment after carbonization, and cleaning, drying and sizing the activated carbon fibers.

[0025] In this embodiment, high-quality mesophase asphalt is preferably selected as the raw material, and the mesophase asphalt is heated to a certain temperature to be in a molten state, wherein the heating temperature is preferably controlled between 180 and 200 degrees, and the heating rate is controlled at 5 to 10 degrees per hour to avoid thermal decomposition or local overheating of the asphalt caused by too fast a temperature rise, and impurities and insolubles therein are removed by a filtering device in the prior art, wherein the filtering device in this embodiment is preferably a filtering device in the prior art that can achieve multi-stage filtration, and large particles of impurities are first filtered through a coarse filter screen arranged inside, and small particles of impurities and suspended matter are removed through a microporous filter membrane of the next stage until the purity of the mesophase asphalt after filtration reaches more than 99.5%, and then the filtered mesophase asphalt is degassed in a vacuum environment, wherein the vacuum degree is preferably set to 0.1-0.5MPa, and maintained for a certain time to allow bubbles and volatile substances in the asphalt to escape, wherein the degassing time is preferably set between 2-4 hours.

[0026] The melt spinning equipment used in this embodiment can select a spinneret with a suitable aspect ratio and aperture according to the characteristics of the mesophase pitch and the limiting diameter requirements. For example, if thinner fibers are required, a spinneret with a larger aspect ratio and a smaller aperture can be selected; if higher strength fibers are required, a spinneret with a smaller aspect ratio and a moderate aperture can be selected.

[0027] In this embodiment, the spinning temperature is preferably controlled between 300 and 350°C, and fine-tuned according to the characteristics of the mesophase pitch and the fiber diameter requirements. The spinning pressure is preferably controlled between 0.5 and 1.0 MPa, and the extrusion speed and fineness of the fiber can be controlled by adjusting the pressure.

[0028] Under the set temperature and pressure conditions, the pretreated mesophase asphalt is extruded through the spinneret to form continuous fibers. During the spinning process, the changes in spinning speed, temperature and pressure are closely monitored, and the process parameters are adjusted in time to ensure the stability of the fiber quality.

[0029] By controlling the spinning speed and cooling conditions, the crystallinity and orientation of the fiber can be adjusted and the mechanical properties of the fiber can be improved. In this embodiment, a roller or mesh belt in the prior art is used as a collecting device to collect the fibers obtained by spinning. At the same time, a preliminary quality inspection is performed on the collected fibers, such as appearance, diameter uniformity, etc., to promptly discover and deal with problems.

[0030] In this embodiment, a pre-oxidation furnace with temperature control and atmosphere adjustment functions is selected. When in use, the fibers obtained by melt spinning are evenly laid on the conveyor belt of the pre-oxidation furnace, while ensuring that there are appropriate gaps between the fibers so that air can circulate fully and the fibers are evenly heated.

[0031] The fiber is placed in a pre-oxidation furnace and heated at a slow and steady rate in an air atmosphere. The heating rate is preferably controlled between 1 - 2 °C / min, and the temperature is gradually raised to a final temperature of 200 - 250 °C. After reaching the pre-oxidation temperature, a certain insulation time is maintained, and the pre-oxidation time is 1 - 2 hours, so that the mesophase asphalt molecules in the fiber can fully undergo oxidation reaction.

[0032] At the same time, during the heat preservation process, the temperature change is closely monitored to ensure the temperature stability. After the pre-oxidation is completed, the fiber is slowly cooled to room temperature, wherein the cooling is preferably carried out by natural cooling or slow ventilation cooling in the prior art. In this embodiment, a carbonization furnace with precise temperature control and inert gas protection function is selected. When in use, the pre-oxidized fibers are placed in the furnace chamber of the carbonization furnace, while ensuring that the fibers are arranged neatly to avoid overlapping and squeezing of the fibers.

[0033] The fiber is placed in a carbonization furnace and heated in an inert gas atmosphere with a heating rate controlled between 2 - 3 °C / min. The temperature is first raised to 600 - 700 °C for low-temperature carbonization and kept at this temperature for 1 - 2 hours to allow the non-carbon elements in the fiber to gradually escape and form a preliminary carbon fiber structure. The temperature is then raised to 1000 - 1200 °C for high-temperature carbonization and kept at this temperature for 2 - 3 hours to further improve the crystallinity and strength of the carbon fiber.

[0034] In the present embodiment, during the carbonization process, an inert gas, such as nitrogen or argon, is continuously introduced, and the flow rate of the inert gas should be adjusted according to the volume of the carbonization furnace and the number of fibers to ensure the stability of the atmosphere in the furnace. After the carbonization is completed, the fiber is slowly cooled to room temperature, and the cooling rate should be controlled within an appropriate range, wherein the cooling is preferably carried out by natural cooling or slow ventilation cooling in the prior art.

[0035] In this embodiment, plasma treatment technology is used to place the carbonized carbon fiber in a plasma treatment device, and the high-energy particles in the plasma are used to bombard the surface of the carbon fiber, so that polar groups and free radicals are generated on the surface, thereby increasing the surface energy. At the same time, plasma treatment can also remove impurities and pollutants on the surface of the carbon fiber, making the surface cleaner. The general treatment time can be set between 30-60 minutes, and the power can be in the range of 500-1000 watts. By controlling the treatment time and power, the bombardment intensity of the plasma on the carbon fiber surface can be adjusted, thereby controlling the number of surface polar groups and free radicals generated.

[0036] More preferably, during the surface treatment process, the chemical composition and structure of the carbon fiber surface are monitored by surface analysis techniques in the prior art, such as X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), etc., to determine whether the effect of the surface treatment reaches the expected effect.

[0037] In this embodiment, a suitable cleaning agent, such as an organic solvent or deionized water, is selected according to the properties of the treatment agent and impurities remaining on the surface of the carbon fiber. The carbon fiber is placed in the cleaning agent for cleaning by adopting methods such as immersion, spraying or ultrasonic cleaning in the prior art. The immersion cleaning time is preferably between 30 and 60 minutes, and the spraying or ultrasonic cleaning time can be appropriately shortened.

[0038] After cleaning, it is dried in a hot air drying oven or a vacuum drying oven in the prior art. According to the characteristics of the carbon fiber and the performance of the drying equipment, the appropriate drying temperature and time are set. Generally speaking, the drying temperature is preferably set between 80-120°C, and the drying time is preferably set between 2-4 hours. At the same time, during the drying process, the stability of the drying environment is ensured to avoid temperature fluctuations or humidity changes from affecting the drying effect of the carbon fiber, and attention is paid to ventilation to discharge gases such as water vapor generated during the drying process.

[0039] After drying, a suitable sizing agent is selected according to the application field of the carbon fiber and the compatibility requirements with the matrix, wherein the sizing agent can be in the form of a polymer solution, emulsion or powder, and is preferably evenly coated on the surface of the carbon fiber by dipping, spraying or brushing.

[0040] When sizing by dipping, the carbon fiber is soaked in the sizing solution for a certain period of time, then taken out and dried; when sizing by spraying or brushing, it is necessary to ensure that the sizing agent is evenly covered on the surface of the carbon fiber. After the sizing is completed, the sizing effect can be checked by measuring indicators such as the bundling of the carbon fiber and the bonding strength with the matrix.

[0041] More specifically, in this embodiment, the distribution of the sizing agent on the surface of the carbon fiber can be determined by microscopic analysis, such as SEM observation. Embodiment 2

[0042] On the basis of Example 1, this embodiment further provides a system for providing the performance of intermediate phase asphalt carbon fiber, including a pneumatic single-hole spinning machine, a spinneret with different aspect ratios and apertures, a plasma surface treatment device and a control module. The spinneret of this embodiment is installed on the spinning machine, wherein the spinning machine adjusts parameters such as temperature, pressure, and air pressure through the control module to control the intermediate phase asphalt to be extruded in the spinneret hole of the spinneret to form continuous fibers. The carbon fiber obtained by spinning enters the surface treatment link. The plasma surface treatment device adjusts parameters such as power, air pressure, and processing time through the control module to perform surface modification on the carbon fiber. The carbon fiber after post-treatment enters the quality inspection link, and the quality inspection results are fed back to the control module to provide a basis for further process optimization.

[0043] In this embodiment, the control module is connected to the pneumatic single-hole spinning machine through an electrical connection or a data transmission line, and can accurately adjust the temperature, pressure, air pressure and other parameters of the spinning machine, and ensure the stability and consistency of the spinning process through a real-time monitoring and feedback system.

[0044] The control module is connected to the plasma surface treatment device through electrical connection or data transmission line, and can adjust the parameters of the device such as power, gas pressure and treatment time to control the degree of modification of the carbon fiber surface by high-energy plasma. At the same time, the equipment that uses surface analysis technology to monitor the treatment effect is also connected to the control module so that the monitoring results can be fed back to the control module for process adjustment.

[0045] In the post-processing stage, the selection of equipment and materials used in the steps of cleaning, drying, sizing, etc. and the parameter control are all adjusted by the control module. For example, the control module can select the appropriate cleaning agent, set the drying temperature and time, select the sizing agent and control the sizing method, etc. according to the needs.

[0046] In this embodiment, the aspect ratio of the spinneret is in the range of 2:1 to 5:1, and the aperture is in the range of 0.1 to 0.5 mm, wherein the material of the spinneret is preferably high temperature resistant and corrosion resistant stainless steel or ceramic material, and the shape of the spinneret hole is circular or elliptical.

[0047] In this embodiment, the plasma surface treatment device is preferably a high-energy plasma source plasma that can generate high energy, wherein these plasmas can modify the surface of the carbon fiber to increase its surface energy and activity. Different types of plasma sources include direct current discharge plasma, plasma generated by high-frequency electromagnetic waves, or microwave plasma.

[0048] By treating in a vacuum environment, the interference of impurities can be reduced and the interaction efficiency between plasma and carbon fiber surface can be improved. By controlling the gas pressure range from 0.01 to 1 Torr, the stability and treatment effect of plasma can be ensured. At the same time, by adjusting the plasma power between 10 and 200 W and the treatment time between 10 and 300 seconds, the bombardment intensity and treatment depth of plasma on the carbon fiber surface can be controlled by adjusting these parameters, thereby achieving different degrees of surface modification. Embodiment 3

[0049] Based on the first and second embodiments, this embodiment further provides a spinneret design for improving the performance of mesophase pitch carbon fibers: Based on the continuity equation, momentum equation and energy equation of fluid mechanics, combined with the characteristics of mesophase asphalt in materials science, the relationship between viscosity and temperature and shear rate, surface tension, etc., a mathematical model of the flow of mesophase asphalt in spinnerets of different shapes and sizes is constructed.

[0050] For the viscosity model, a power law model or a Carreau model can be used, and the model parameters can be determined by fitting the experimental data.

[0051] In this embodiment, the inlet velocity distribution is set, and the average velocity and velocity distribution function at the inlet are determined according to the actual extrusion equipment and process parameters. More specifically, for a circular spinneret, the inlet velocity can be assumed to be uniformly distributed or parabolically distributed; the outlet is usually assumed to be atmospheric pressure, or the outlet pressure is determined according to the actual subsequent process requirements, and a no-slip boundary condition is adopted, that is, the velocity of the fluid at the wall is zero.

[0052] Select a suitable numerical method to solve the writing model, namely, the finite element method, the finite difference method, and the finite volume method in the prior art.

[0053] Use computer simulation software, such as ANSYS Fluent, COMSOL Multiphysics, etc., to perform numerical simulation on spinneret holes of different shapes and sizes, and establish a geometric model of the spinneret holes, which can be different shapes such as circular, elliptical, rectangular, and with different apertures and aspect ratios; divide the mesh: use a suitable mesh division method to ensure that there is sufficient mesh density in key areas to improve the accuracy of the simulation; set simulation parameters: including the physical properties parameters of the intermediate phase asphalt, boundary conditions, initial conditions, numerical methods, etc.

[0054] In order to increase the accuracy of the constructed model, this example also simulates different spinning conditions: Temperature: Change the spinning temperature within a certain range to study the effect of temperature on the flow of mesophase pitch and outlet swelling effect.

[0055] Pressure: Change the pressure at the inlet and analyze the effect of pressure on fiber extrusion speed and outlet expansion.

[0056] Extrusion speed: Adjust the speed parameters of the extrusion equipment and observe the effect of extrusion speed on the flow of mesophase asphalt and fiber diameter.

[0057] In this embodiment, the output simulation results include: Velocity field: displays the velocity distribution of the mesophase pitch in the spinneret, including axial velocity, radial velocity and tangential velocity.

[0058] Pressure field: gives the pressure distribution inside the spinneret hole, which helps to understand the flow resistance and extrusion pressure of the mesophase asphalt.

[0059] Temperature field: optional output of temperature distribution results.

[0060] Fiber Diameter and Shape: Predict the diameter and shape of the fiber at the exit, and evaluate the effect of different spinneret hole shapes and sizes on fiber quality.

[0061] The parameter sensitivity analysis includes: Change the shape, size, aspect ratio and other parameters of the spinneret hole and observe the influence of these parameters on the outlet swell effect.

[0062] Analyze the sensitivity of spinning conditions (temperature, pressure, extrusion speed) to the die swell effect and identify the key influencing factors.

[0063] Through parameter sensitivity analysis, we can determine which parameters are most important for controlling the outlet swell effect, and provide guidance for the design optimization of the spinneret.

[0064] More specifically, in this embodiment, according to the results of numerical simulation, several representative spinneret hole shapes and sizes are selected, and the spinneret is manufactured by precision machining technology to ensure the quality and accuracy of the spinneret, so as to ensure the reliability of the experimental results.

[0065] Use a pneumatic single-hole spinning machine or other suitable spinning equipment, conduct experiments according to predetermined spinning conditions, control parameters such as spinning temperature, pressure and extrusion speed, and make them as consistent as possible with the conditions of numerical simulation, use microscopes, laser diameter gauges and other measuring instruments to measure the carbon fiber obtained by spinning, obtain the diameter, shape, outlet expansion rate and other parameters of the fiber, compare them with the numerical simulation results, compare the experimental results with the numerical simulation results, and analyze the differences between the two. If there is a large difference between the experimental results and the simulation results, it is necessary to correct and optimize the mathematical model, such as adjusting the viscosity model parameters, improving the boundary conditions, etc. Through experimental verification, the accuracy and reliability of the mathematical model can be continuously improved, providing a more accurate basis for the optimization design of the spinneret.

[0066] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.

Claims

1. A method for improving the performance of mesophase pitch carbon fiber, characterized in that: include: Selecting mesophase asphalt as raw material for pretreatment; Melting the pretreated mesophase pitch into spinning fibers; Performing a pre-oxidation treatment on the spinning to form pre-oxidized fibers; The pre-oxidized fibers are fed into a carbonization furnace for carbonization and activation after carbonization; The activated carbon fibers are cleaned, dried and sized.

2. A method for improving the performance of mesophase pitch carbon fiber according to claim 1, characterized in that: The raw material pretreatment includes: heating the mesophase asphalt to a set temperature to make it in a molten state, removing impurities and insolubles in the middle by a filtering device in the molten state, and transferring the filtered mesophase asphalt to a vacuum container for degassing.

3. A method for improving the performance of mesophase pitch carbon fiber according to claim 2, characterized in that: Select spinnerets with different aspect ratios and apertures, design the spinnerets according to the outlet expansion effect, optimize the radial structure of the fiber, improve the fiber uniformity by adjusting the spinning parameters, and extrude the pretreated mesophase asphalt through the spinneret holes to form continuous fibers.

4. A method for improving the performance of mesophase pitch carbon fiber according to claim 3, characterized in that: The pre-oxidation treatment includes: evenly laying the fibers obtained by melt spinning on the conveyor belt of the pre-oxidation furnace, ensuring that there are gaps between the fibers for air circulation, sending the fibers into the pre-oxidation furnace for heating, and controlling the heating rate between 1 degree and 2 degrees per minute until it rises to 200 degrees to 250 degrees.

5. A method for improving the performance of mesophase pitch carbon fibers according to claim 4, characterized in that: The carbon treatment includes: placing the pre-oxidized fiber inside a carbonization furnace to heat it up, controlling the heating rate to be 2 to 3 degrees per minute, first controlling the temperature to be carbonized at a low temperature of 600 to 700 degrees, and holding the temperature for 1 to 2 hours, then raising the temperature to 1000 to 1200 degrees, and setting the holding time to be 2 to 3 hours.

6. A method for improving the performance of mesophase pitch carbon fibers according to claim 5, characterized in that: The activation treatment includes: placing the carbon-treated carbon fiber in a plasma treatment device, turning on the device to bombard the surface of the carbon fiber with high-energy particles to generate polar groups and free radicals on the surface, and the bombardment time is set to 30 to 60 minutes and the power is set to 500 to 1000 watts.

7. A method for improving the performance of mesophase pitch carbon fibers according to claim 6, characterized in that: The cleaning, drying and sizing of the activated carbon fiber specifically include: Cleaning: Select a suitable cleaning agent and use one or more methods of immersion, spraying or ultrasonic cleaning. The cleaning time is 30 to 60 minutes; Drying: drying the cleaned carbon fiber in one or more ways of a hot air drying oven or a vacuum drying oven, wherein the drying temperature is set at 80 to 120 degrees and the drying time is set at 2 to 4 hours; Sizing: Select a suitable sizing agent and use one or more methods of dipping, spraying or brushing to apply sizing, and after the sizing is completed, dry it until the slurry is completely dry.

8. The system for improving the performance of mesophase pitch carbon fiber according to any one of claims 1 to 7, characterized in that: include: a) a gas pressure single hole spinning machine for preparing mesophase pitch carbon fiber by spinning process; b) manufacturing spinnerets with different aspect ratios and apertures to optimize the radial structure of the fiber; c) a plasma surface treatment device including a high energy plasma source for modifying the surface of carbon fibers to increase their surface energy and activity; d) Control module, used to adjust spinning parameters and surface treatment parameters, including temperature, pressure, air pressure, power and treatment time, to achieve process optimization.

9. A system for improving the performance of mesophase pitch carbon fibers according to claim 8, characterized in that: The method of making spinnerets with different aspect ratios and apertures specifically comprises: The shape and size of the spinneret holes of the spinneret are determined according to the mathematical model. Through numerical simulation and experimental verification, the control effects of spinnerets with different shapes and sizes on the outlet swell effect are compared. According to the experimental results, the spinneret design is adjusted until the expected outlet swell control effect is achieved.

10. The system for improving the performance of mesophase pitch carbon fibers according to claim 8, characterized in that: The plasma surface treatment method specifically includes: a) Adjust the plasma power to 10 to 200 W; b) Processing in a vacuum environment with a pressure range of 0.01 to 1 Torr; c) The processing time is between 10 and 300 seconds.

Citation Information

Patent Citations

  • Preparation method of novel mesophase pitch-based composite carbon fibers

    CN104213253A